'You've Been Framed': A critical review of academic discourse on philanthrocapitalism. (4th May 2021) - Haydon, Steph; Jung, Tobias; Russell, Shona
Abstract: Philanthrocapitalism—the strategic application of market methods and motives for philanthropic purposes—plays increasingly prominent roles in policy design and implementation at national and international levels. Notwithstanding philanthrocapitalism's growing significance, relevant scholarly discourse remains limited and fragmented. Drawing together diverse debates, our paper systematically reviews and synthesizes academic literature on philanthrocapitalism. Alongside raising questions about the casting and practice of philanthropy, the 186 relevant publications included in our review indicate a strong emphasis of philanthrocapitalism in the areas of education, international development, healthcare and agriculture. Across these, we identify and discuss the importance of three cultural frames: (1) development challenges being framed as scientific problems; (2) beneficiaries being framed as productive entrepreneurs; and (3) philanthropy being framed as social investment. Outlining and critically examining these issues, this work contributes: a comprehensive analysis of key debates and issues; strengthened conceptual clarity and nuance through an evaluative exploration of the multiple interpretations of philanthrocapitalism; and a future research agenda to address persisting knowledge gaps and refine focus.